The teaching profession and teacher education in Singapore (1950 to present): from surviving to thriving - Liu, Woon Chia (Revista Española de Educación Comparada, 2023)
Teaching is a highly regarded profession in Singapore. Achieving such a status was a result of a series of strategic polices passed by the government to improve public education in Singapore. In tandem with Singapore’s priority in developing human capital, improving the quality of teachers is considered essential to achieving the goal of providing quality education to every child. To develop a better understanding of Singapore’s journey in teachers being viewed as professionals today, it is necessary to examine key developments in both Singapore’s education system and teacher education programmes. Based on these two overarching themes, the author will discuss some of the key policies that were incepted to guide Singapore’s success towards providing quality education for its learners (students and teachers). For a small nation with no natural resources, a concerted effort by the Ministry of Education, Academy of Singapore Teachers, and National Institute of Education is deemed necessary to achieve her educational goals. Looking beyond the 21stcentury, the article will also share some of the current strategies that aim to equip Singapore teachers with the attitudes, skills, and knowledge to help their students tackle the challenges of living in a volatile, uncertain, complex, and ambiguous world. To realise this vision, the National Institute of Education adopts the Model of Teacher Education for the 21st Century (TE21) that aims to prepare autonomous thinking teachers for the 21st century through a new paradigm of teacher education that is supported by a robust partnership with education stakeholders, and a strong theory-practice link in teacher education programmes. Through these insights, we hope to provoke reflection, stimulate discussion, and encourage educational stakeholders across the globe to draw out promising strategies for improving teacher education worldwide